Strengthening of polyamide 6 and isosorbide-containing copolyester immiscible blends by in-situ reactive compatibilization. (16th January 2023) - Jang, Dong Jin; Lee, Joo Hyung; Lee, Jae Jin; Hyun, Jieun; Kim, Seong Hun
Abstract: Polyamide 6 (PA6) is a representative engineering plastic and is used in various fields due to its impact, chemical, and weather resistance. In industrial applications that require high impact strength, glass-fiber-reinforced PA6 is often used. It is important to note, however, that due to the high hardness of glass fibers, screws and injection molds are very easily worn during extrusion and injection. Poly (ethylene glycol 1, 4-cyclohexanedimethylene isosorbide terephthalate) (PEICT) is a copolyester containing isosorbide derived from biomass and has the characteristics of high impact resistance. In this study, PA6 and PEICT blends were prepared by melt processing. A reactive compatibilizer with multifunctional epoxy groups was introduced to reduce the interfacial tension of immiscible PA6 and PEICT. The epoxy groups reacted with the terminal groups of blend components to form branched PA6-co-PEICT copolymers. The copolymers inhibited the aggregation of PEICT and improved the interfacial adhesion between PA6 and PEICT, effectively performing compatibilization. In the successful PA6/PEICT blend, an impact strength of 29.59 kJ/m 2 was achieved, comparable with glass fiber reinforced PA6. Graphical abstract: Image 1 Highlights: Reactive compatibilization of PA6 and PEICT blends was achieved with the aid of a multifunctional epoxy polymer. The ADR was predicted to be located at the interface between the PA6 and the PEICT. For the PA6/PEICT/ADR blend, an impact strength of 29.59 kJ/m 2 was achieved. A facile, high-impact-resistant PA6 blend has been demonstrated in this study.